2018
DOI: 10.1115/1.4038760
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Model for Turbulent Heat Flux in High-Speed Flows With Shock-Induced Flow Separation

Abstract: High-speed flows with shock waves impinging on turbulent boundary layers pose severe challenge to current computational methods and models. Specifically, the peak wall heat flux is grossly overpredicted by Reynolds-averaged Navier–Stokes (RANS) simulations using conventional turbulence models. This is because of the constant Prandtl number assumption, which fails in the presence of strong adverse pressure gradient (APG) of the shock waves. Experimental data suggest a reduction of the turbulent Prandtl number i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The value of σ, as shown in Equation 4, for the PSP direction at the centerline with respect to the measurem Pathak et al [19] indicated that the constant value of r is questionable for a flow with SIBLS; i.e., the value of r is lower in a strong adverse pressure gradient; the opposite trend may be true in the presence of a favorable pressure gradient. An example (M = 0.83 and λ = 10 • ) of the difference between the PSP and Kulite measurements, ∆(p w /p o ) p-k (= p psp − p kulite /p o ), is shown in Figure 13.…”
Section: Error Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The value of σ, as shown in Equation 4, for the PSP direction at the centerline with respect to the measurem Pathak et al [19] indicated that the constant value of r is questionable for a flow with SIBLS; i.e., the value of r is lower in a strong adverse pressure gradient; the opposite trend may be true in the presence of a favorable pressure gradient. An example (M = 0.83 and λ = 10 • ) of the difference between the PSP and Kulite measurements, ∆(p w /p o ) p-k (= p psp − p kulite /p o ), is shown in Figure 13.…”
Section: Error Analysismentioning
confidence: 99%
“…where T a and M a are, respectively, the temperature and Mach number in the external flow. Note that r depends on the local flow characteristics (subsonic/transonic flow, favorable/adverse pressure gradient) [19]. The error, σ, for all PSP data points with respect to Kulite sensors is calculated by:…”
mentioning
confidence: 99%
“…A similar trend is reported by Pirozzoli et al 35 for a turbulent boundary-layer at Mach 2.25 and Gaviglio 36 for a turbulent boundary-layer at Mach 9.4. Based on our previous work 37 we highlighted that the log-region (0.05< y/δ <0.25) of boundary-layer is most important to model wall heat flux and we take an average value of R uT = −0.7 in our current simulations. We follow the procedure laid out earlier and start with Eq.…”
Section: Effect Of Upstream Velocity Fluctuationmentioning
confidence: 99%